Penguatan Pendidikan Lingkungan Hidup dan Budaya Hijau Di SDN Kemiri 3 Menuju Green School - Anton Prayitno; Djohar Noeriati Retno Dahoelat (Sasambo: Jurnal Abdimas (Journal of Community Service), 2019)
Elementary School 3 of kemiri, located in Jabung District, is a school that is experiencing difficulties in developing Green school programs. the surface of the land in the schoolyard is rarely found. Most of the teachers assume that the program must require sufficient land and land media. Limited land and several facilities in the learning process to realize the green school program requires the right solution. Hydroponic technology has been known as an alternative technology for crop cultivation in limited land. In hydroponic technology, there is plant cultivation technology without the use of soil. The utilization of used objects as planting media can be arranged in stages with a vertical garden (vega) pattern, which is called vega hydroponic technology. Therefore, the purpose of this activity is to provide strengthening of environmental education through planting with hydroponic technology. To achieve the targets and outcomes, the activities carried out are as follows: 1) counseling the school about the importance of environmental education, 2) Training on management and cultivation of various types of vegetable and ornamental plants with vega hydroponic technology to create a green, and beautiful school;3) Hydroponic technology installation with vertical garden patterns, and 4) Assistance in planting vegetables and ornamental with vertical garden pattern hydroponic technology. In addition, the average pretest obtained by the teacher was 6.87, while the average understanding of students was 5.5. While the results of the post-test, the understanding of the teacher and students were 8.37 and 6.625. This shows that there is an increase in teacher understanding by 1.5 points and 1.13 points for students so that students' and teachers' knowledge of environmental education has increased.